Analysis of the Effect of Dribbling Training on the Technical Performance of Soccer Players: A Systematic Literature Review - Yudha Hafid; Martin Sudarmono (Indonesian Journal for Physical Education and Sport, 2025)
This study aims to analyze the effect of dribbling training on the technical abilities of soccer players. This study uses the PRISMA standard in conducting systematic reviews and meta-analyses. The articles reviewed were publications between 2020 and 2024. The search process used the keywords "Dribbling", "Football", and "Technical Performance". From the database search, 103 articles were found. After being adjusted to the inclusion criteria, 10 articles were selected for further analysis. Training techniques, physical agility, and eye-to-toe coordination affect the dribbling ability of a footballer. To improve dribbling speed and effectiveness, athletes need good physical strength and motor skills. In one-on-one situations, dribbling possession is essential as a technical-tactical strategy to create goal opportunities and dismantle the opponent's defense.